Konsep Diri dan Kecemasan Sosial Pada Mahasiswa - Kholisa, Intan Nurul; Purnamasari, Santi Esterlita; Rinaldi, Martaria Rizky (Syiah Kuala Psychology Journal, 2024)
Social interaction is a fundamental need for university students, who are in the early adulthood developmental stage where the ability to adapt and control anxiety is crucial. Many students experience social anxiety that can hinder their ability to interact effectively. This study aims to determine the relationship between self-concept and social anxiety among early adult university students in Yogyakarta. This research employs a quantitative method with a correlational design. The subjects of this study consisted of 110 students aged 19-28 years, selected using a convenience sampling technique. Data were collected using a social anxiety scale and a self-concept scale. The data analysis method used was Karl Pearson's product moment, resulting in a correlation coefficient of rxy = -0.664 (p 0.000), indicating a negative relationship between self-concept and social anxiety among early adult university students in Yogyakarta. The conclusion of this study is that the more positive the students' self-concept, the lower the level of social anxiety they experience; conversely, the more negative the students' self-concept, the higher the level of social anxiety they experience.Interaksi sosial merupakan kebutuhan fundamental bagi mahasiswa yang berada pada tahap perkembangan dewasa awal, karena kemampuan menyesuaikan diri dan mengendalikan kecemasan sangat penting. Banyak mahasiswa mengalami kecemasan sosial yang dapat menghambat kemampuan mereka untuk berinteraksi secara efektif. Penelitian ini bertujuan untuk mengetahui hubungan antara konsep diri dan kecemasan sosial pada mahasiswa dewasa awal di Yogyakarta. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional. Subjek penelitian ini terdiri dari 110 mahasiswa berusia 19-28 tahun yang dipilih menggunakan teknik convenience sampling. Data dikumpulkan menggunakan Skala Kecemasan Sosial dan Skala Konsep Diri. Metode analisis data menggunakan product moment dari Karl Pearson, dan hasilnya diperoleh koefisien korelasi sebesar rxy = -0,664 (p 0,000), yang berarti ada hubungan negatif antara konsep diri dengan kecemasan sosial pada mahasiswa dewasa awal di Yogyakarta. Kesimpulan dari penelitian ini adalah semakin positif konsep diri mahasiswa maka semakin rendah tingkat kecemasan sosial yang mereka alami, dan sebaliknya, semakin negatif konsep diri mahasiswa maka semakin tinggi tingkat kecemasan sosial yang mereka alami.